Analysis of employee workload optimization on manual packing operators in the preparation of goods “all type 20 gr gusset bag” by using the workload analysis method in PT XYZ - Hati, Shinta Wahyu; Septiani, Nurulia (Social Sciences Insights Journal, 2024)
PT. XYZ is a manufacturing company that produces chemicals, namely industrial glue located in Batamindo Industrial Park, Muka Kuning, Batam. The packing department is an important department in the production process if in this process there are obstacles and problems there will be delays in delivery. One of the concerns is the workload in the gusset bag packing process. Workload is measured based on the work station and each individual packing operator. By making observations using the workload analysis (WLA) method which is seen from several assessment factors such as identification of productive and non-productive activities, productive percentage, performance rating, and allowance or allowance, the workload value in the gusset bag packing process can be known. The observation results show that the finish goods packing station experiences an overload workload of 135%. The workload at this station is high because this process requires extra energy to do a lot of job desc compared to other stations. For workload per individual operator, it is known that operators who have worked longer have a high workload than new operators. The workload for the workstation is more influenced by the high allowance factor and for the operator workload the influencing aspect is the performance rating.